2014
DOI: 10.1111/tog.12109
|View full text |Cite
|
Sign up to set email alerts
|

Early abdominal ectopic pregnancy: challenges, update and review of current management

Abstract: Key content Early abdominal ectopic pregnancy (EAP), though rare, has a high mortality rate. There are no pathognomic symptoms of abdominal pregnancy. Symptoms are akin as for other types of ectopic pregnancy, thus a high index of suspicion is necessary for diagnosis. The tool of choice for diagnosis is ultrasound but it only gives 50% accuracy when used along with clinical evaluation. On occasion, magnetic resonance imaging may help to diagnose EAP. Medical management is commonly used where potential life‐t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
80
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(82 citation statements)
references
References 38 publications
2
80
0
Order By: Relevance
“…Risk factors for abdominal pregnancy are similar to those of any ectopic pregnancy and include low-socioeconomic status, PID, endometriosis, previous pelvic surgery, intrauterine contraceptive devices and history of ectopic pregnancy 7 8 15 21. The patient described here was not from a low socioeconomic group, although she did have a history of PID, which may have contributed to her risk of developing this rare form of ectopic pregnancy.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Risk factors for abdominal pregnancy are similar to those of any ectopic pregnancy and include low-socioeconomic status, PID, endometriosis, previous pelvic surgery, intrauterine contraceptive devices and history of ectopic pregnancy 7 8 15 21. The patient described here was not from a low socioeconomic group, although she did have a history of PID, which may have contributed to her risk of developing this rare form of ectopic pregnancy.…”
Section: Discussionmentioning
confidence: 82%
“…A recent review of 225 abdominal pregnancies reported the most common sites as (from most frequent to least): the pouches around the uterus (most commonly the Pouch of Douglas), the adnexae, omentum, bowel/appendix, liver, spleen, retroperitoneum and the abdominal wall 9. In addition, implantation sites at the diaphragm and renal fascia have been described 15 18 19…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Depending on the gestational period at which they detected, the abdominal pregnancy can also be classified into early abdominal pregnancy, i.e., detected at or before 20 weeks of gestation, and advanced abdominal pregnancy, i.e., detected after 20 weeks of gestation. 12 In this case, it was the advanced abdominal pregnancy identified after 38 weeks of pregnancy, which is a rarer condition compared to the early abdominal pregnancy.…”
Section: Discussionmentioning
confidence: 86%
“…[21] A report from Nigeria places the frequency in that country at 34 per 100,000 deliveries and a report from Zimbabwe, 11 per 100,000 deliveries. [5][22] [23] The maternal mortality rate is estimated to be about 5 per 1,000 cases, about seven times the rate for ectopics in general, and about 90 times the rate for a delivery (1987 US data). [21] History Albucasis (936-1013), an Arab Muslim physician is credited with first recognizing abdominal pregnancy which was apparently unknown to Greek and Roman physicians and was not mentioned in the writings of Hippocrates; Jacopo Berengario da Carpi (1460-1530) the Italian physician is credited with the first detailed anatomical description of abdominal pregnancy.…”
Section: Differential Diagnosismentioning
confidence: 99%